Imagens alquímicas renascentistas: um estudo preliminar do manuscrito La génération et opération du grand oeuvre pour faire de l or (1620) - Stagni, Reno (2008)
The objective of this study is to analyze, among the multiple aspects that permeate the alchemical tradition, one that treats the relation between image and text as a way to the knowledge stored in the books, and to try to evidence some aspects of the use of the image as a tool to decode the verbal text. Therefore it was chosen, as case study, the manuscript La Génération et Opération du Grand OEuvre pour Faire de l Or (The Generation and Operation of the Great Work to Make Gold), anonymous manuscript, copied in the first quarter of the XVII century, whose comparison with alchemical works related to that same period provided the analysis, object of this study